Death of the black widow [compact disc, unabridged] - Patterson, James, 1947-; Barker, J. D. (Jonathan Dylan), 1971- (Hachette Audio, 2022)
"On his first night with Detroit PD, Officer Walter O'Brien is called to a murder scene. A terrified twenty-year-old has bludgeoned her kidnapper with skill that shocks even O'Brien's veteran partner. The young woman is also a brilliant escape artist. Her bold flight from police custody makes the case impossible to solve, and, for Walter, even more impossible to forget. By the time Walter's promoted to detective, his fascination with the missing, gray-eyed woman is approaching obsession. And when Walter discovers that he's not alone in his search, one truth is certain. This deadly string of secrets didn't begin in his home city, but he's going to make sure it ends there."--Container.